Study on the Influence of Various Types of Taijiquan on Senior Citizens Based on STROOP Color-Word Test - Hui-Xin Zhou , Sheng-wen Zhou (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are various types and diversified forms of Taijiquan. Different types of Taijiquan. differ greatly from one another in the amount and intensity of exercise. This paper conducts Stroop Color-Word Test (CWT) on 120 senior citizens in Yongzhou, Hunan Province after intervention of Taijiquan.in three different periods, and average values and standard deviations are calculated in Excel 2013 with the assistance of SPSS based on the data and indexes collected in each period. Verified by statistics and analyzed by two-way RM ANCOVA, it shows in the study that Stroop has generally been improved after intervention of Taijiquan., and there is no obvious difference in the indexes of both males and females after exercise, but evident differences come out in the results of the three different periods of the 56-form Taijiquan., displaying an more effective effect. Therefore, through the Stroop CWT on senior citizens after a 12-week exercise of Taijiquan., this paper hopes to provide theoretical foundation for senior citizens more specifically so as to help them prevent cognitive disorder and senile dementia more effectively.